Imaging Modalities to Identity Inflammation in an Atherosclerotic Plaque - Sunny Goel; Avraham Miller; Chirag Agarwal; Elina Zakin; Michael Acholonu; Umesh Gidwani; Abhishek Sharma; Guy Kulbak; Jacob Shani; On Chen (Radiology Research and Practice)
Atherosclerosis is a chronic, progressive, multifocal arterial wall disease caused by local and systemic inflammation responsible for major cardiovascular complications such as myocardial infarction and stroke. With the recent understanding that vulnerable plaque erosion and rupture, with subsequent thrombosis, rather than luminal stenosis, is the underlying cause of acute ischemic events, there has been a shift of focus to understand the mechanisms that make an atherosclerotic plaque unstable or vulnerable to rupture. The presence of inflammation in the atherosclerotic plaque has been considered as one of the initial events which convert a stable plaque into an unstable and vulnerable plaque. This paper systemically reviews the noninvasive and invasive imaging modalities that are currently available to detect this inflammatory process, at least in the intermediate stages, and discusses the ongoing studies that will help us to better understand and identify it at the molecular level.